Motivation Counts: Autonomous But Not Obligated Sharing Promotes Happiness in Preschoolers - Wu, Zhen; Zhang, Zhen; Guo, Rui; Gros-Louis, Julie (Frontiers in Psychology, 2017)
Research has demonstrated that prosocial sharing is emotionally rewarding, which leads to further prosocial actions; such a positive feedback loop suggests a proximal mechanism of human’s tendency to act prosocially. However, it leaves open a question as to how the emotional benefits from sharing develop in young children and whether sharing under pressure promotes happiness as well. The current study directly compared 3- and 5-year-old Chinese children’s happiness when sharing was autonomous (the recipient did not contribute to getting the reward) with when sharing was obligated (the recipient and the actor jointly earned the reward). We found that children shared more items overall when sharing was obligated than autonomous, demonstrating their conformity to social norms of merit-based sharing. In children who eventually shared with others, 5-year-olds gave out more stickers in the obligated sharing condition than in the autonomous sharing condition, but 3-year-olds shared the same amount between the conditions, suggesting that 5-year-olds adhered to the merit-based sharing norm more strictly than 3-year-olds. Moreover, in the autonomous sharing condition, children displayed greater happiness when they shared with the recipient than when they kept stickers for themselves, suggesting that costly prosocial giving benefited children with positive mood; however, children did not gain happiness when they shared with the recipient in the obligated sharing condition. These findings demonstrate that children’s affective benefits depend on the motivation underlying their prosocial behavior, and further imply that normative force and emotional gains may independently drive preschoolers’ prosocial behaviors.